Message from the FFCN Symposium Chairs (2016 IEEE Trustcom/BigDataSE/ISPA, 2016)
Presents the introductory welcome message from the conference proceedings. May include the conference officers' congratulations to all involved with the conference event and publication of the proceedings record.